Engineering Fundamentals: An Introduction to Engineering, 6th Edition - Saeed Moaveni (Cengage Learning, 2019)
Develop strong problem-solving skills and the solid foundation in fundamental principles needed to become an analytical, detail-oriented and creative engineer with Moaveni's ENGINEERING FUNDAMENTALS: AN INTRODUCTION TO ENGINEERING, 6th Edition. This reader-friendly presentation opens with an overview of what engineers do today and offers behind-the scenes glimpses into various areas of specialization. Candid, straight-forward discussions examine what engineers truly need to succeed in today's times. This edition covers basic physical concepts and laws most important for engineering studies and on-the-job success. Readers learn how these principles relate to engineering in practice as Professional Profiles highlight the work of successful engineers around the globe. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.